2023
DOI: 10.3389/fmicb.2023.1097595
|View full text |Cite
|
Sign up to set email alerts
|

Environmental factors contributing to the convergence of bacterial community structure during indigo reduction

Abstract: Indigo is solubilized through the reducing action of the microbiota that occurs during alkaline fermentation of composted leaves of Polygonum tinctorium L. (sukumo). However, the environmental effects on the microbiota during this treatment, as well as the mechanisms underlying the microbial succession toward stable state remain unknown. In this study, physicochemical analyses and Illumina metagenomic sequencing was used to determine the impact pretreatment conditions on the subsequent initiation of bacterial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 52 publications
(84 reference statements)
1
7
0
Order By: Relevance
“…As an initial step in the fermentation, sukumo was treated with hot wood ash extract (60-80 • C, pH > 10.5). It has been reported that high pH has a larger impact on the microbiota in sukumo than in a high-temperature treatment (60 • C) [10]. High temperature is effective if combined with high pH.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…As an initial step in the fermentation, sukumo was treated with hot wood ash extract (60-80 • C, pH > 10.5). It has been reported that high pH has a larger impact on the microbiota in sukumo than in a high-temperature treatment (60 • C) [10]. High temperature is effective if combined with high pH.…”
Section: Discussionmentioning
confidence: 97%
“…Small-scale batch experiments have shown that indigo-reducing bacterial communities are constructed within five days by replacing the initially appearing aerobic microbes. In addition, the changing velocity of the microbiota is faster until approximately day 30, regardless of the timing of wheat bran introduction [10,13]. This is probably because the influence of the substrates derived from sukumo was effective for approximately 30 days.…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations